A Study of Scams and Frauds using Social Engineering in “The Kathmandu Valley” of Nepal - Maharjan, Amit (My University, 2023)
Social Engineering scams are common in Nepal. Coupled with inability of government to enforce policies over technology giants and large swaths of population that are uneducated, social engineering scams and frauds are a real issue. The purpose of the thesis is to find out the extent and impact of social engineering attacks in “The Kathmandu valley” of Nepal. The Kathmandu valley consists of 3 cities including the capital city of Nepal. To conduct the research, the newspaper “The Kathmandu Post” from the year 2019 to 2022 was downloaded and searched for keywords “scam” and “fraud”. After which the results were manually examined to separate news reports of social engineering attacks in Nepal and other countries. Also, a survey was conducted by visiting parks in the Kathmandu valley. A total of 149 people were interviewed to collect data by asking 21 questions regarding social engineering attack faced by the interviewee. Further, literature review of the research papers published related to social engineering and phishing was conducted. The main finding of the thesis was that public awareness program are effective reducing the extent and impact of social engineering attacks in Nepal. The survey suggests large percentage of population have become victims of social engineering attack attempts. More than 70 percent have received messages on WhatsApp regarding fake lottery wins.
Keywords: social engineering, phishing, scams and fraud survey, newspaper report analysis